Model Sinergilitas through Triple Helix Competitive Advantage Of SMEs In Samosir - Nurafrina Siregar; Irawan Irawan (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
This research aims to find out the effect of the synergy model of Triple Helix on Competitive Advantage. This research uses the SEM-Partial Least Square (PLS) approach, which is a component-based or variant-based structural equation model. Hypothesis testing is done using the Bootstrap method with a minimum number of bootstraps as much as 217. The results of this study prove that Academic Collaboration has a positive and significant effect on Competitive Advantage which proves the hypothesis is accepted. This means that the better academic collaboration that can be implemented, the higher the creation of Competitive Advantage. The test results provide empirical evidence that Industry Collaboration had a positive and insignificant effect on Competitive Advantage which proved the hypothesis was rejected. Surely these findings show how Industry Collaboration cannot affect Competitive Advantage so SMEs are expected to evaluate better Industry Collaboration. The test results provide empirical evidence that Government Collaboration has a positive and significant effect on Competitive Advantage which proves the hypothesis is accepted. Surely these findings show how Government Collaboration can affect Competitive Advantage so that SMEs are expected to be able to take advantage of support from the government so that Competitive Advantage can be improved.